2021
DOI: 10.1017/jfm.2021.377
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent and wave kinetic energy budgets in the airflow over wind-generated surface waves

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 107 publications
(215 reference statements)
1
9
0
Order By: Relevance
“…Yang & Shen 2010). A similar feature was observed for the total turbulence production in the tank experiment by Yousefi, Veron & Buckley (2021). Since the change in the turbulent stress is relatively small during the gust, the time variation of is caused primarily by the mean shear evolution near the wave surface (figure 22).…”
Section: Resultssupporting
confidence: 83%
“…Yang & Shen 2010). A similar feature was observed for the total turbulence production in the tank experiment by Yousefi, Veron & Buckley (2021). Since the change in the turbulent stress is relatively small during the gust, the time variation of is caused primarily by the mean shear evolution near the wave surface (figure 22).…”
Section: Resultssupporting
confidence: 83%
“…where q is the TKE, taking a value of (u u + v v + w w )/2 with v v = (u u + w w )/2 (Yousefi et al 2021). The data show similar magnitudes for the vertical advection A 1 and the horizontal advection A 2 (figure 16).…”
Section: Advection Termmentioning
confidence: 78%
“…The needed spatial resolution is typically smaller than what PIV can offer while maintaining a field of view (FOV) large enough to resolve different wave phases. Therefore, the turbulent dissipation rate is often estimated as a part of the residual term in TKE budget analysis (Yousefi et al 2021). This approach presents challenges in a complete analysis of TKE budget, as the residual includes measurement uncertainty and other non-resolvable terms such as pressure transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Grare, Lenain & Melville 2018; Hao & Shen 2019; Husain et al. 2019; Yousefi, Veron & Buckley 2020, 2021; Aiyer, Deike & Mueller 2023, among others). These studies have shown that the drag at the ocean surface strongly depends on environmental conditions and is a function of not only wind speed but also wave height, wave slope, wind–wave alignment and wave age, which is defined as the ratio of the wave phase speed to the reference wind speed measured at a height of 10 m above the air–water interface.…”
Section: Introductionmentioning
confidence: 99%